(untitled) (Acta Scientiarum. Animal Sciences, 2026)
This study aimed to evaluate the effect of dry matter content on the feeding behavior and milk production of Holstein cows. The study was conducted on lactating, multiparous Holstein cows. To assess feeding behavior, automatic feeders (Intergado®, Brazil) were used. The duration of rumination and activity was quantified using electronic collars (Chip Inside, Brazil). The diets were classified according to their dry matter content: high (> 60%), medium (45 to 59%), and low (< 45%). The NCSS statistical program (2005) was employed for statistical analysis. The data were subjected to analysis of variance (GLM-ANOVA), and when statistical differences were identified (p < 0.05), the Tukey-Kramer test was performed for mean comparisons. The Holstein cows that received a diet with a low dry matter content (< 45%) exhibited a reduction in intake (p < 0.001), an increase in milk production (p < 0.001), an extension in rumination time, and a reduction in activity time (p < 0.002). In conclusion, variations in the dry matter content of the diet have an impact on the feeding behavior and milk production of Holstein cows.